A study on the working characteristics of free piston linear generator with dual cylinder configuration by different secondary injection strategies. (15th October 2021) - Yan, Xiaodong; Feng, Huihua; Zuo, Zhengxing; Zhang, Zhiyuan; Wu, Limin; Shi, Cheng
Abstract: Aiming at the dead center change of free piston linear generator with dual-cylinder configuration(FPLGDC), this paper proposes stratified combustion technology and studies the influence of secondary injection timing and injection ratio on the formation and combustion characteristics of stratified mixture. The results show as the secondary injection timing was advanced from 16 o CABTDC to 36 o CABTDC, local over-concentrated mixture in-cylinder was diluted, and the overall uniformity of the mixture was improved. Further, the overall evaporation increased from 89% to 97%. More, as secondary injection ratio decreased from 20% to 10%, the fuel evaporation ratio increased from 14% to 16%, and the stratification of the in-cylinder mixture at the ignition time was more obvious. Therefore, advancing the time of secondary injection and reducing secondary injection ratio can make the mixture more properly stratified, shorten the rapid combustion period, and improve combustion quality. Further, compared with the secondary injection ratio was 20% for secondary injection time at 16 o CABTDC, the peak pressure in the cylinder increased by 14%, and the peak pressure position increased by about 2 o CA when the secondary injection ratio was 10% at a secondary injection time of 36 o CABTDC. Thus, reasonable control the injection strategy can significantly improve the dynamic performance of FPLGDC. Highlights: The influence of secondary injection strategy on the working characteristics of free piston linear generator is studied. Reducing the quality of secondary injection fuel can increase the peak pressure of free piston linear generator. The Combustion period of free piston linear generator is shortened with the advance of the second injection time. The secondary injection strategy realizes the stratified mixture and lean burn.